Crk and CrkL as Therapeutic Targets for Cancer Treatment - Park, Taeju (Cells, 2021)
Crk and CrkL are cellular counterparts of the viral oncoprotein v-Crk. Crk and CrkL are overexpressed in many types of human cancer, correlating with poor prognosis. Furthermore, gene knockdown and knockout of Crk and CrkL in tumor cell lines suppress tumor cell functions, including cell proliferation, transformation, migration, invasion, epithelial-mesenchymal transition, resistance to chemotherapy drugs, and in vivo tumor growth and metastasis. Conversely, overexpression of tumor cells with Crk or CrkL enhances tumor cell functions. Therefore, Crk and CrkL have been proposed as therapeutic targets for cancer treatment. However, it is unclear whether Crk and CrkL make distinct or overlapping contributions to tumor cell functions in various cancer types because Crk or CrkL have been examined independently in most studies. Two recent studies using colorectal cancer and glioblastoma cells clearly demonstrated that Crk and CrkL need to be ablated individually and combined to understand distinct and overlapping roles of the two proteins in cancer. A comprehensive understanding of individual and overlapping roles of Crk and CrkL in tumor cell functions is necessary to develop effective therapeutic strategies. This review systematically discusses crucial functions of Crk and CrkL in tumor cell functions and provides new perspectives on targeting Crk and CrkL in cancer therapy.